PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL PASSING BAWAH BOLA VOLI SISWA KELAS VIII B SMP NEGERI 22 KOTA JAMBI 2024 - Ratna Padhillah; Reza Hadinata; Anggrawan Janur Putra (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study used the Classroom Action Research (CAR) method which was conducted in two cycles. Each cycle consists of planning, action, observation, and reflection stages. Data were collected through teacher and student observation sheets, as well as volleyball underhand passing skills tests. Data analysis was conducted quantitatively and qualitatively to evaluate the effectiveness of the PBL model in improving learning outcomes. The results showed that the implementation of the PBL model significantly improved student learning outcomes. Before the implementation of PBL, only 10% of students achieved the KKM. After cycle I, this percentage increased to 50%, although there were still obstacles. In cycle II, after improvements were made with the use of video media and more intensive guidance, the completion rate increased to 80%. In addition, the observation results showed that 80% of learning aspects had been fulfilled by the teacher, while 76% of students were in the good category and 20% were in the very good category, so that all students met the KKM. Thus, the Problem Based Learning (PBL) model has proven effective in improving understanding, underhand passing skills, and active participation of students in volleyball learning.